MiRNA expression affects survival in patients with obstructive sleep apnea and metastatic colorectal cancer - Piera Soccio; Giorgia Moriondo; Giulia Scioscia; Pasquale Tondo; Giuseppina Bruno; Guido Giordano; Roberto Sabato; Maria Pia Foschino Barbaro; Matteo Landriscina; Donato Lacedonia (Non-coding RNA Research)
Introduction: The relationship between obstructive sleep apnea (OSA) and cancer has been recognized for some time now. However, little is known about the mechanisms by which sleep apnea promotes tumorigenesis and the impact of OSA on survival after cancer diagnosis. In the last few years, research has focused on the exploration of different biomarkers to understand the mechanisms underlying this relationship and miRNAs, non-coding single strands of about 22 nucleotides that post-transcriptionally regulate gene expression, have emerged as possible actors of this process.The aim of the study was to evaluate the impact of OSA on survival of metastatic colorectal cancer (mCRC) patients based on the expression of specific miRNAs. Methods: The expression of 6 miRNAs, respectively miR-21, miR-23b, miR-26a, miR-27b, miR-145 and miR-210, was analyzed by qRT-PCR in patients’ sera. Response to first-line therapy, Kaplan-Meier curves of overall and progression-free survival were used to evaluate survival in mCRC patients with and without OSA stratified for the expression of miRNAs. Results: The expression of miR-21, miR-23b, miR-26a and miR-210 was significantly upregulated in mCRCs with OSA compared to no OSA. In mCRC patients with OSA and increasing expression of miR-21, miR-23b, miR-26a and miR-210 risk of progression after first-line therapy was higher and both overall and progression-free survival were significantly worst. Conversely, as miR-27b and miR-145 expression increased, the life expectancy of patients diagnosed with OSA and mCRC improved markedly. Conclusions: This study highlights the relevance of specific miRNAs on OSA in mCRCs and their significance as non-invasive biomarkers in predicting the prognosis in patients with mCRC and OSA.